NETWORK PHARMACOLOGY ANALYSIS OF BIOACTIVE COMPOUNDS OF RED BETEL (Piper crocatum Ruiz dan Pav) STEM AS AN ANTI-INFLAMMATORY AGENT - Sari, Putri Kharisma Novita; Febyaningrum, Vitasigi Dwi (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
Inflammation is a mechanism in the body's defense system that occurs through the release of pro-inflammatory mediators. However, inflammation needs to be controlled because it triggers excessive production of inflammatory mediators that cause tissue damage and disease progression. Various types of first-line anti-inflammatory therapy drugs have potential for adverse side effects such as anemia, hypertension, and immunosuppression, so alternative anti-inflammatory agents are needed that are considered safe and effective. The red betel plant (Piper crocatum Ruiz and Pav) is known to contain secondary metabolites such as sesquiterpenes, aldehydes, phytosterols, and sterols that are already known as anti-inflammatory agents. This study aims to determine the anti-inflammatory potential of the red betel plant based on pharmacological network analysis. The test compounds are secondary metabolites that were successfully detected in the red betel stem such as caryophyllene, octadecadienal, stigmasterol, and sitosterol. Proteins related to anti-inflammatory activity obtained from GeneCards, proteins interacting with test compounds predicted by SwissTargetPrediction, and the results of the intersection of both types of proteins were further analyzed using STRING with Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment methods. GO and KEGG enrichment analysis showed involvement in NF-?B, IL-17, PI3K/AKT, and TNF signaling pathways, with 16 key genes related to anti-inflammatory activity targets. The main target proteins of caryophyllene and stigmasterol being HSP90AA1 and STAT3, respectively, while octadecadienal and sitosterol showed NFKB1 as the same main target protein. The results provide a scientific data for the use of these secondary metabolites as anti-inflammatory agents.